OCENA WARTOŚCI – NIEZBĘDNY ETAP OCHRONY ZABYTKÓW ARCHEOLOGICZNYCH - Marek Konopka (Ochrona Dziedzictwa Kulturowego, 2016)
In 2012 and 2015, Zbigniew Kobyliński’s articles on valuing archaeological monuments and sites (the article of 2012 was co-authored by Jacek Wysocki) were printed in post-conference publications. Z. Kobyliński assumed that historic preservation officers can assess values of archaeological sites by basing on non-scientific criteria and the level of preservation of artifacts only. The author is also of the opinion that the criteria used for classifying and categorising both properties of special architectural and historic interest and works of arts cannot be applied to archaeological sites. This stems from the knowledge on full potential of archaeological monuments and sites being limited prior to conducting thorough analyses. According to Kobyliński, any value assessment results in negative selection of archaeological sites and therefore, it is of utmost importance to provide all resources with appropriate protection. The author of this article takes a different point of view. Assuming that there is 0.5 million sites entered into the Polish record of archaeological monuments and sites, Konopka is of the opinion that it is and will be impossible to provide all resources even with basic monitoring, not mentioning active care. He reckons that basing on the information collected by archaeologists, it is possible to nominate sites of outstanding potential. Analysing the records by applying the most innovative non-invasive methods may allow for selecting sites which should be provided with particular care in a certain region. Konopka calls for implementing a form in which past relics of outstanding historical value and features characteristic of archaeological sites would be listed. These would be useful in identifying the potential of the place to be protected. He suggests creating a card being of higher rank than the record. The information provided therein would be helpful in nominating properties and sites to be entered into the register of historic monuments and sites.